Effectiveness of the hypnoteaching learning model in Javanese language learning - Damayanti, Eliza Naviana; Sukoyo, Joko (Universitas Dian Nuswantoro, 2025)
Education aims to create a learning process that allows students to be active in developing their potential. However, many schools still use conventional learning models such as the lecture method, which often makes students passive and afraid to ask questions, thereby reducing their learning outcomes. In the modern era, hypnoteaching has emerged as an innovative approach that is believed to be more effective. This research explores the effectiveness of hypnoteaching in learning Javanese at the junior high school level. The type of research used was an experiment with a posttest-only control group design. The research subjects were class IX students at SMP Negeri 10 Salatiga, where class IX G was the experimental group that applied hypnoteaching, while class IX E was the control group using the conventional model. The results showed that the average post-test score for the experimental group was 81.29, while the control group was only 58.06. Analysis using the T-test shows a significant value of p = 0.000 (α < 0.05), which shows that hypnoteaching is more effective in improving student learning achievement compared to conventional models. However, it's important to note that this study has some limitations, such as the small sample size and the specific context of Javanese language learning, which may affect the generalizability of the results.